Techno-economic feasibility assessment of sorption enhanced gasification of municipal solid waste for hydrogen production - Santos, Mónica P. S.; Hanak, Dawid P. (Elsevier, 2022)
Waste-to-fuel coupled with carbon capture and storage is forecasted to be an effective way to mitigate the greenhouse gas emissions, reduce the waste sent to landfill and, simultaneously, reduce the dependence of fossil fuels. This study evaluated the techno-economic feasibility of sorption enhanced gasification, which involves in-situ CO2 capture, and benchmarked it with the conventional steam gasification of municipal solid waste for H2 production. The impact of a gate fee and tax levied on the fossil CO2 emissions in economic feasibility was assessed. The results showed that the hydrogen production was enhanced in sorption enhanced gasification, that achieved an optimum H2 production efficiency of 48.7% (T = 650 °C and SBR = 1.8). This was 1.0% points higher than that of the conventional steam gasification (T = 900 °C and SBR = 1.2). However, the total efficiency, which accounts for H2 production and net power output, for sorption enhanced gasification was estimated to be 49.3% (T = 650 °C and SBR = 1.8). This was 4.4% points lower than the figure estimated for the conventional gasification (T = 900 °C and SBR = 1.2). The economic performance assessment showed that the sorption enhanced gasification will result in a significantly higher levelised cost of hydrogen (5.0 €/kg) compared to that estimated for conventional steam gasification (2.7 €/kg). The levelised cost of hydrogen can be reduced to 4.5 €/kg on an introduction of the gate fee of 40.0 €/tMSW. The cost of CO2 avoided was estimated to be 114.9 €/tCO2 (no gate fee and tax levied). However, this value can be reduced to 90.1 €/tCO2 with the introduction of an emission allowance price of 39.6 €/tCO2. Despite better environmental performance, the capital cost of sorption enhanced gasification needs to be reduced for this technology to become competitive with mature gasification technologies.
Keywords: Waste-to-fuel; Modelling; Waste management; Hydrogen production; CO2 capture